Respuesta :
Answer:
√113
or
10.6301458127
Step-by-step explanation:
Plug the coordinated into this equation and make sure you match up the corrdinates in the correct order
d = √(x2 - x1)^2 + (y2 - y1)^2
The number next to the number does NOT mean multiply it mean like this
(x2, y2) and (x1, y1) so you would plug them in like this:
d = √(-6 - 2)^2 + (4 - (-3))^2
d = √(-8)^2 + (7)^2
d = √(64 + 49
d = √113
or 10.6301458127
Answer with Step-by-step explanation:
The distance(d) between the points (a,b) and (c,d) is given by:
[tex]d=\sqrt{(c-a)^2+(d-b)^2}[/tex]
Here, we have to find distance between (2,-3) and (-6,4)
(a,b)=(2,-3) and (c,d)=(-6,4)
[tex]d=\sqrt{(-6-2)^2+(4-(-3))^2}[/tex]
[tex]d=\sqrt{8^2+7^2}[/tex]
[tex]d=\sqrt{64+49}[/tex]
[tex]d=\sqrt{113}[/tex]
Hence, the distance between the points (2 -3) and (-6 4) on the coordinate plane is:
[tex]\sqrt{113}[/tex]